Fracture resistance of three different all-ceramic crowns: In vitro study - Alarwali, Ammar M.; Kutty, Muralithran Govindan; Al-Haddad, Afaf Y.; Gonzalez, Maria Angela G. (Mosher and Linder, 2018)
Purpose: To evaluate the fracture resistance and failure mode of three different all-ceramic crowns; CEREC Bloc, IPS e.Max Press and Cercon in a simulated clinical situation. Methods: 30 extracted maxillary premolars were prepared and randomly assigned to three groups equally according to the type of crown used. The first was the CEREC group: monolithic feldspathic crowns (CEREC Blocs). The second was the E.Max group: monolithic lithium disilicate crowns (IPS e.Max Press). The third group was the Cercon group: bilayered partially stabilized zirconia crowns (Cercon). All crowns were cemented using dual-cured resin cement (ParaCore). The specimens were then subjected to thermocycling (5-55°C/500 cycles) and loaded to failure at an angle of 45° to the occlusal surface of the crown. Failure data was statistically analyzed using one-way ANOVA and Tukey's HSD post hoc test at a= 0.05. Fractographic analysis was performed to determine the fracture modes of the failed specimens. Results: The mean fracture values for CEREC, E.Max and Cercon groups were 387 ± 60 N, 452 ± 86 N, and 540 ± 171 N, respectively. Significant differences were found between CEREC and Cercon groups (P< 0.05). Catastrophic fracture within the ceramic crown was the major failure mode of the CEREC group. For E.Max and Cercon groups, the major failure mode was exhibiting severe tooth fracture while the ceramic crown remained intact.